Testing guidelines and strategies by ICMR: a roadmap to handle COVID-19 pandemic in India - Mantri, Neha; Gupta, Manoj Kumar; Bhardwaj, Pankaj; Goel, Akhil D.; Saurabh, Suman; Jain, Vidhi; Nag, Vijay Lakshmi; Misra, Sanjeev (International Journal Of Community Medicine And Public Health, 2022)
Background: Since the inception of the COVID-19 pandemic, the cases are continuously increasing in India. Though this growth of the cases was relatively slower during the initial phase of the pandemic, now the cases are increasing rapidly and positioned the country at third place in the world in the COVID-19 tally. This study was done to review all the guidelines and strategies released by the ICMR and MoH and FW, Government of India, in regard with the testing of COVID-19 in the country and to collate them with timelines. Methods: Country-level data was retrieved from the crowdsourced database and was analyzed descriptively to calculate the cumulative and per day test positivity rates. Results: A sharp rise in the test positivity rate was observed until the first week of April, which declined slightly during the next month. After that, the test positive rate is found to be continuously increasing. At the same time, the testing capacity of the country has also increased from about 250 tests per day at the beginning of March to 6.42 lac per day by the end of July. ICMR put a lot of effort into the expansion of the laboratory network to ramp up the COVID-19 testing capacity in the country. Without having any delay, dynamic guidelines, and strategies for testing with a lot of innovations were developed and implemented maintaining all the quality and safety parameters. Conclusions: ICMR worked tirelessly on the forefront to devise a roadmap to handle the COVID-19 pandemic in India through the development of testing strategies and guidelines.